2016
DOI: 10.2147/dmso.s95120
|View full text |Cite
|
Sign up to set email alerts
|

Role of sleep quality in the metabolic syndrome

Abstract: Emerging evidence has assigned an important role to sleep as a modulator of metabolic homeostasis. The impact of variations in sleep duration, sleep-disordered breathing, and chronotype to cardiometabolic function encompasses a wide array of perturbations spanning from obesity, insulin resistance, type 2 diabetes, the metabolic syndrome, and cardiovascular disease risk and mortality in both adults and children. Here, we critically and extensively review the published literature on such important issues and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 151 publications
(79 citation statements)
references
References 441 publications
(556 reference statements)
2
73
0
4
Order By: Relevance
“…There is increasing recognition that disturbances of sleep are risk factors for obesity and cardiometabolic disturbances [42]. The associations between sleep parameters and metabolic risk factors are more conflicting in children and adolescents compared to adults.…”
Section: Additional Components Of the Mets In Children And Adolescentsmentioning
confidence: 99%
See 3 more Smart Citations
“…There is increasing recognition that disturbances of sleep are risk factors for obesity and cardiometabolic disturbances [42]. The associations between sleep parameters and metabolic risk factors are more conflicting in children and adolescents compared to adults.…”
Section: Additional Components Of the Mets In Children And Adolescentsmentioning
confidence: 99%
“…In addition, Wang et al [45] demonstrated that both short and overlong sleep duration are associated with a higher risk of overweight/obesity in preschool-aged children and with an impairment of their lipid profile. Detailed pathophysiological pathways for these associations are unknown at present, but leptin levels and different compositions of diets seem to play a role [42]. …”
Section: Additional Components Of the Mets In Children And Adolescentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides sleep duration, poor sleep quality has been associated with an increased risk of metabolic syndrome (Koren, Dumin, & Gozal, 2016;Mesas et al, 2014), yet not in all studies (Petrov et al, 2013).…”
Section: Introductionmentioning
confidence: 98%